Kelah sang demang Jahja Datoek Kajo : pidato otokritik di Volkstraad [i.e. Volksraad], 1927-1939 - Etek, Azizah; Mursyid A. M.; Arfan B. R. (Yogyakarta : LKiS, 2008)
Account of Jahja Datoek Kajo, a nationalist from Minangkabau, Sumatera Barat Province and member of Volksraad, a kind of parliament in Indonesia during the Dutch colonial period.
Includes bibliographical references (page 505-506) and index.
Keywords: Jahja -- Datoek Kajo, -- 1874-1942.; Sumatera Barat (Indonesia) -- History -- 20th century; Indonesia -- History -- 20th century